A pesticide monitoring survey in rivers and lakes of northern Greece and its human and ecotoxicological risk assessment - Papadakis, Emmaluel N.; Vryzas, Zisis G.; Kotopoulou, Athena; Kintzikoglou, Katerina; Makris, Konstantinos C. (My University, 2015)
A pesticide monitoring study covering the main rivers and lakes of Northern Greece (Macedonia, Thrace and Thessaly) was undertaken. A total of 416 samples were collected over a 1.5-year sampling period (September 1999– February 2001) from six rivers and ten lakes. The water samples were analyzed with an off-line solid phase extraction technique coupled with a gas chromatography ion trap mass spectrometer using an analytical method for 147 pesticides and their metabolites, including organochlorines, organophosphates, triazines, chloroacetanilides, pyrethroids, carbamates, phthalimides and other pesticides (herbicides, insecticides and fungicides). Based on the pesticide survey results, a human health carcinogenic and non-carcinogenic risk assessment was conducted for adults and children. Ecotoxicological risk assessment was also conducted using default endpoint values and the risk quotient method. Results showed that the herbicides metolachlor, prometryn, alachlor and molinate, were the most frequently detected pesticides (29%, 12.5%, 12.5% and 10%, respectively). They also exhibited the highest concentration values, often exceeding 1 μg/L. Chlorpyrifos ethyl was the most frequently detected insecticide (7%). Seasonal variations in measured pesticide concentrations were observed in all rivers and lakes. The highest concentrations were recorded during May–June period, right after pesticide application. Concentrations of six pesticides were above the maximum allowable limit of 0.1 μg/L set for drinking water. Alachlor, atrazine and a-HCH showed unacceptable carcinogenic risk estimates (4.5E-06, 4.6E-06 and 1.3E-04, respectively). Annual average concentrations of chlorpyriphos ethyl (0.031 μgL), dicofol (0.01 μg/L), dieldrin (0.02 μg/L) and endosulfan a (0.065 μg/L) exceeded the EU environmental quality standards. The risk quotient estimates for the insecticides chorpyrifos ethyl, diazinon and parathion methyl and herbicide prometryn were above acceptable risk values. The coupling of monitoring data to probabilistic human and ecotoxicological risk estimates could find use by Greek regulatory authorities, proposing effective pollution management schemes.
Keywords: Pesticides; Rivers; Lakes; Greece; Health risk assessment; Ecotoxicological risk assessment